Twister trouble - Schreiber, Ann.; Speirs, John.; Cole, Joanna (New York : Scholastic, 2000)
While on their way to Weatherama Amusement Park to attend the Wild Weather Show, Ms. Frizzle and her class get a first-hand lesson in the forces of nature as they fly directly into the heart of a powerful tornado.
"Based on The Magic School Bus books written by Joanna Cole and illustrated by Bruce Degen"-- T.p. verso.
3.
006-009.
Accelerated Reader AR
Keywords: Tornadoes -- Juvenile fiction